Can Beta-2-Adrenergic Pathway Be a New Target to Combat SARS-CoV-2 Hyperinflammatory Syndrome?—Lessons Learned From Cancer - Barbieri, Antonio; Robinson, Nirmal; Palma, Giuseppe; Maurea, Nicola; Desiderio, Vincenzo; Botti, Gerardo (Frontiers in Immunology, 2020)
SARS-CoV-2 infection is a new threat to global public health in the 21stcentury (2020), which has now rapidly spread around the globe causing severe pneumonia often linked to Acute Respiratory Distress Syndrome (ARDS) and hyperinflammatory syndrome. SARS-CoV2 is highly contagious through saliva droplets. The structural analysis suggests that the virus enters human cells through the ligation of the spike protein to angiotensin-converting enzyme 2 (ACE2). The progression of Covid-19 has been divided into three main stages: stage I- viral response, stage II – pulmonary phase, and stage III – hyperinflammation phase. Once the patients enter stage III, it will likely need ventilation and it becomes difficult to manage. Thus, it will be of paramount importance to find therapies to prevent or slow down the progression of the disease toward stage III. The key event leading to hyperinflammation seems to be the activation of Th-17 immunity response and cytokines storm. Β2-adrenergic receptors (Β2AR) are expressed on airways and on all the immune cells such as macrophages, dendritic cells, B and T lymphocytes. Blocking (Β2AR) has been proven, also in clinical settings, to reduce Th-17 response and negatively modulate inflammatory cytokines including IL-6 while increasing IFN𝛾. Non-selective beta-blockers are currently used to treat several diseases and have been proven to reduce stress-induced-inflammation and reduce anxiety. For these reasons, we speculate that targeting Β2AR in the early phase of Covid-19 might be beneficial to prevent hyperinflammation.